RONC-14. REPLICATING CLINICAL RADIATION THERAPY PROTOCOLS IN PRECLINICAL BRAIN TUMOUR MODELS. Issue 2 (22nd June 2018) - Endersby, Raelene; Hii, Hilary; Strowger, Brooke; Ancliffe, Mathew; Seymour, Tracy; Gottardo, Nicholas
Abstract: Surgical resection and radiotherapy, often followed by chemotherapy, have been the mainstay of paediatric brain cancer treatment for decades. For brain cancers with a predilection to spread throughout the brain and spinal cord, such as medulloblastoma, craniospinal irradiation represents the standard-of-care. An unavoidable consequence of this is collateral damage of healthy tissue, resulting in potentially devastating long-term sequelae, including suboptimal cognitive development. Animal models that accurately recapitulate the genotypes and phenotypes of paediatric brain cancers are essential to evaluate potential new approaches to therapy ahead of clinical trial. The XRAD image-guided small animal radiotherapy (SmART) system combines CT imaging with precision irradiation using x-rays. Our aim was to optimise preclinical radiotherapy protocols in mouse models of medulloblastoma, ependymoma and glioblastoma. To evaluate the accuracy and efficacy of the device, radiation was administered to mice with orthotopically-implanted brain tumours. Tissue was harvested, and markers of DNA damage and apoptosis used to evaluate tumour targeting. A transgenic model of SHH-subtype medulloblastoma (NeuroD2::SmoA1) demonstrated exquisite sensitivity to irradiation with significant DNA damage and apoptosis two hours post-treatment. Moreover, reduced tumour size was evident by MRI after five days of radiotherapy. Multiple patient-derived xenograft (PDX) models of Group 3 medulloblastoma also demonstrated radiation sensitivity, whereas minimal anti-tumour effects were observed in ependymoma and glioblastoma xenografts. These data serve as baseline information for future experimental protocols that will evaluate combinatorial regimens of radiotherapy, conventional chemotherapy, and novel anti-cancer agents. These experiments enable rigorous evaluation and selection of viable agents to consider for future clinical evaluation.